An Action Pattern Model of Inter‐firm Cooperation* - Lui, Steven S.; Ngo, Hang‐yue (Journal of Management Studies, 2005)
abstract An action pattern model was developed and applied to the examination of inter‐firm cooperative processes. The model considered cooperation as a continuous cycle of actions and reactions between cooperating partners. The building blocks of the model include cooperative equilibrium, disruptive events, action types and action patterns. Three action pattern variables were proposed to describe the interactions. It was hypothesized that action patterns are contingent on partner relationships and the transaction cost characteristics of a partnership. The hypotheses were tested on a sample of 263 partnerships in the construction industry in Hong Kong. The quantitative study was supplemented by four in‐depth case studies. The results show that: (1) trust was an important antecedent of action patterns; and (2) transaction cost variables moderate the relationships between partner relationships and action patterns. These findings suggest that future research should give more attention to the interaction of partners during cooperation.